The Influence of Financial Literacy and Parental Income on Lifestyle Through Students' Financial Management Behaviour - Rahmad Nur Karim; Suroto Suroto; Fanni Rahmawati; Widya Hestiningtyas (Soedirman Economics Education Journal, 2026)
This study is motivated by the importance of fostering a frugal lifestyle among students, given that consumptive behaviour remains prevalent due to low financial literacy, differences in family economic conditions, and limited personal financial management skills. The study aims to analyse the influence of financial literacy and parental income on frugal living, with financial management behaviour serving as a mediating variable. Employing a descriptive-verificative quantitative approach with an ex post facto design, the research population comprised 84 eleventh-grade Accounting students at SMK Negeri 1 Bukit Kemuning, selected via saturated sampling. Data were collected using questionnaires and analysed using path analysis in SPSS. The results indicate that financial literacy and parental income have significant effects on financial management behaviour, and that parental income also significantly influences lifestyle. However, financial management behaviour does not have a substantial impact on lifestyle. These findings highlight that a frugal lifestyle can be shaped through strong financial literacy and adequate family economic support.